Correlation of liver elastography with lipid profile, liver function test, and HbA1c in type II diabetes with non-alcoholic fatty liver disease in Hospital Universiti Sains Malaysia - Subbramaniam, Subashini A/P (2016)
Background Non-alcoholic fatty liver disease (NAFLD) is a range of liver disorders which ranges from simple accumulation of fat in the hepatocytes (steatosis) to macrovescicular steatosis, periportal and lobular inflammation (steatohepatitis). The current gold standard to diagnose liver diseases is biopsy, however this has two major problems: it is dependent on the sampling area, which may cause an evaluation error in the case of mild fatty liver, and it is an invasive technique which carries a morbidity rate of 1-5% and a mortality rate of 0.01-0.1%. Non-invasive imaging tools such as shear wave elastrography has been proven to be useful for screening and categorizing of chronic liver disease, however, further evaluation of this tool is needed in different population. Aim and Objective This study aimed to assess the associations among liver elastography, lipid profile, liver function test and HbA1c among type II diabetic patient in Hospital Universiti Sains Malaysia, in which (i) the prevalence and incidence rate of NAFLD and liver fibrosis/cirrhosis among type II diabetic patient in Hospital Universiti Sains Malaysia was determined, respectively; (ii) the mean values of the blood lipid profile, liver functions test and HBA1c among patient with and without NAFLD were compared; and(iii) the associations between degree of liver elasticity; and blood lipid profil, liver function test and HBA1c were investigated. Method Patients were recruited from Diabetic Clinic, HUSM. Only patients who fulfilled the selection criteria and provided written consent were enrolled into this study. The Medical record of the patient was provided by the clinic. Liver elastrography was performed in Radiology Department, HUSM by Supersonic Imagine Using Shear Wave Elastography (Siemens Acuson Antares -Premium Edition, Camberley, UK), equipped with Aixplorer Multiwave. Data were recorded and analysed using SPSS version 22.0. Result The prevalence of NAFLD among participant with DM type II was 87%, while the incidence rate of liver fibrosis among the patients with NAFLD was 11.7% (8/68). The distribution of METAVIR score among T2DM patients were F0 (60/68), F1 (7/68), and F2 (1/68). The result revealed very poor correlation between SWE values and part of the study parameters, which includes HDL, LDL, TG, AST and HbA1c (P>0.05). However, there were two parameters showed significant weak association between SWE values; TC (r=0.283; P=0.019) and ALT (r=0.252; P=0.038). Conclusion This study had determined to the prevalence of NAFLD and incidence rate of liver fibrosis among T2DM patients admitted to HUSM. The prevalence of NAFLD was higher but the incidence rate of liver fibrosis was lower compared to previous study.